"Bring on Sector Two!" The sounds of bent and broken circuits. Issue 1 (2nd January 2016) - Pinch, Trevor
Abstract: This paper presents an ethnographic investigation of the electronic music practice of circuit-bending. It argues that circuit-benders use sonic skills in rendering desirable sounds from old, discarded and broken devices. The paper is based upon the author's own experiences with bent and broken circuits and upon interviews with circuit-benders. The paper argues that the interest in circuit-bending lies in its double challenge to conventional meanings of technology and to conventional meanings of musical instruments. It shows how circuit-benders share the aspirations of fields such as Science and Technology Studies (STS) in deriving new meanings of technology, in challenging linear and deterministic views of technological development, and in wrestling with the agency of non-humans. It explores the contradictions and paradoxes in using circuit-bent devices as musical instruments given conventional musical notions of control and the prerequisites of live performance. It contrasts and compares the artistic aims of circuit-benders with the more academic goals of academic analysis.